COVID-19: A 2020 update - Bhuiyan, M. Nadir (Indian J Med Sci, 2020)
The 2019 COVID-19 pandemic has thrown the global health-care system into a chaotic flux. Consolidating and reviewing all available knowledge will be crucial to combating the spread of this novel coronavirus. Prevention is paramount, but health care workers are at increased risk, and protective supplies are being limited and being rationed. Common symptoms include fever, cough, and shortness of breath. Hospitalizations are estimated to occur in about 20% of cases and are mostly due to pneumonia.([1]) While multiple promising treatments are being reported in the medical literature; there is limited, reliable clinical data are available. To minimize exposure of medical staff to contagious patients and to provide rapid escalation of care to these patients, a telehealth strategy could be leveraged. Such a strategy would entail the use of both telemedicine visits for communication and digital health platforms for monitoring.